2021
DOI: 10.1177/11795441211028751
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease in Rheumatoid Arthritis: Risk Factors, Autoantibodies, and the Effect of Antirheumatic Therapies

Abstract: Objective: To scope the current published evidence on cardiovascular risk factors in rheumatoid arthritis (RA) focusing on the role of autoantibodies and the effect of antirheumatic agents. Methods: Two reviews were conducted in parallel: A targeted literature review (TLR) describing the risk factors associated with cardiovascular disease (CVD) in RA patients; and a systematic literature review (SLR) identifying and characterizing the association between autoantibody status and CVD risk in RA. A narrative synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 78 publications
(187 reference statements)
0
5
0
1
Order By: Relevance
“…However, some observational studies have drawn different conclusions. Fazeli Y et al found that the pathogenesis of the atherosclerosis process preceded the diagnosis of RA (24). Another study demonstrated that coronary artery calcification was no higher in RA patients compared to non-RA patients (64% vs. 52%, P = 0.31) (25).…”
Section: Discussionmentioning
confidence: 97%
“…However, some observational studies have drawn different conclusions. Fazeli Y et al found that the pathogenesis of the atherosclerosis process preceded the diagnosis of RA (24). Another study demonstrated that coronary artery calcification was no higher in RA patients compared to non-RA patients (64% vs. 52%, P = 0.31) (25).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that the onset of atherosclerosis precedes that of RA 27 , and there is an increasing belief that atherosclerosis is becoming a primary cause of rheumatoid arthritis 28 . In contrast, several cross-sectional studies have found that the incidence of coronary atherosclerosis, peripheral atherosclerosis, aortic valve sclerosis, and carotid atherosclerosis in RA patients is greater than that in the general population, sometimes even doubling [29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…The anti-CCP autoantibodies and RF autoantibodies have a synergistic effect in mediating RA-associated inflammation and disease activity, and their presence was associated with a higher rate of CAC and CAD in patients with RA. [30][31][32] Choi and colleagues demonstrated in their study that methotrexate-treated patients had a 70% reduction in cardiac events compared with those not receiving the same therapy regularly. 33 Other disease-modifying drugs such as sulfasalazine, penicillamine, hydroxychloroquine, and gold did not confer this protection.…”
Section: Discussionmentioning
confidence: 99%